A Comparative Study on Hydroxyl and Ether Functionalized Ionic Liquid Additives for Defect Passivation and Stability in Perovskite Solar Cells - Varlıklı, Canan; Siyahjani Gültekin, S.; Turgut, S.B.; Ozdemir, Saliha; Gültekin, B.; Varlikli, C. (Royal Soc Chemistry, 2025)
This study systematically investigates the effects of two ionic liquid (IL) additives, 2-(2-methoxyethoxy)-N,N-bis(2-(2-methoxyethoxy)ethyl)-N-methylethanaminium iodide (EtAI) and 2-hydroxy-N,N-bis(2-hydroxyethyl)-N-methylethanaminium iodide (HOAI), on the structural, morphological, optical, and photovoltaic properties of triple-cation perovskite thin films. FT-IR, XRD, XPS, SEM, and AFM analyses were employed to characterize additive-induced modifications, while UV-Vis, PL, and TRPL measurements were utilized to evaluate their optical properties. SEM and AFM results reveal that the hydroxyl (-OH) groups in HOAI and etheric groups in EtAI significantly improve film morphology by enhancing grain size, reducing surface roughness, and refining grain boundaries, thereby promoting more efficient charge transport. Photovoltaic characterization revealed that the film with 3 mmol HOAI exhibited a maximum reverse-scan power conversion efficiency (PCE) of 17.65%, retaining approximately 85% of its initial efficiency after 1000 hours under ambient conditions. In contrast, the film with 1 mmol EtAI achieved a reverse-scan PCE of 17.17%, although higher EtAI concentrations adversely affected stability. These findings provide valuable insights into the interplay between additive chemistry and perovskite film quality, offering a promising route for improving the efficiency and long-term performance of perovskite solar cells. This record is sourced from MEDLINE/PubMed, a database of the U.S. National Library of Medicine